Clinical, Immunological, And Genetic Characterization Of Colombian Patients With Cutaneous Recalcitrant Warts - Rojas, Julián; Velásquez, Margarita María; Jouanguy, Emmanuelle; López, Juan Álvaro; Franco, José Luisa; Arias, Andrés Augusto (Iatreia, 2022)
Inborn errors of innate and intrinsic immunity are monogenic diseases that result in a predisposition to a whole spectrum of infectious diseases, including viral infections. Cutaneous warts caused by Human Papillomavirus (HPV) infection have a 10% incidence in the general population. These lesions are relatively common, and most warts revert spontaneously. However, in otherwise healthy individuals, these warts persist for > 2 years without response to conventional therapy (cryotherapy, salicylic acid, or bleomycin), and they are called recalcitrant warts (RW). Host defense against HPV relies on intact and functioning cellular immunity including T cell, natural killer cell cytotoxicity, and intrinsic immunity. Therefore, in patients in whom warts are recalcitrant, concern for immune defects is raised.